Air Transport Implications in Tourist Destinations. The Trapani Airport in Western Sicily - Calderon, Enrique; Ventura, Paolo; Massaro, Alessandro (TeMA - Journal of Land Use, Mobility and Environment, 2019)
This search following the Sicily, the largest island in the Mediterranean Sea (25,460 sq km) and a self-governing Region, located in the southernmost part of Italy, has at least four tourist-related airports, sited between the eastern and western coast, separated from each other by a vast territory without efficient transport links and suffering from many diverse environmental problems. Utilizing a desk search methodology based on GIS software, this paper discusses the impact upon the regional development of the tourist traffic of the Trapani Airport situated in the westernmost part of Sicily. Ultimately it analyzes the critical role of connectivity and accessibility in the development of the area and tourism, seeking a maximum involvement of stakeholders. The recent growth of low-cost carriers have had a definite impact on the economic growth of the entire territory, where those choices could determine the life or the death of firms and, inevitably, their annual incomes. Tourism and connectivity are strictly related, thus showing deficiencies of the area in terms of accessibility, as well as the trade-offs between the different government (central and local) investment policies and the specific benefits emerging from the airport in the regional mobility.